Nutrient sources differ in the fertilised eggs of two divergent broiler lines selected for meat ultimate pH - Angélique Petit; Sophie Réhault-Godbert; Lydie Nadal-Desbarats; Estelle Cailleau-Audouin; Pascal Chartrin; Emilie Raynaud; Justine Jimenez; Sophie Tesseraud; Cécile Berri; Elisabeth Le Bihan-Duval; Sonia Métayer-Coustard (Scientific Reports, 2022)
Abstract The pHu+ and pHu− lines, which were selected based on the ultimate pH (pHu) of the breast muscle, represent a unique model to study the genetic and physiological controls of muscle energy store in relation with meat quality in chicken. Indeed, pHu+ and pHu− chicks show differences in protein and energy metabolism soon after hatching, associated with a different ability to use energy sources in the muscle. The present study aimed to assess the extent to which the nutritional environment of the embryo might contribute to the metabolic differences observed between the two lines at hatching. Just before incubation (E0), the egg yolk of pHu+ exhibited a higher lipid percentage compared to the pHu− line (32.9% vs. 27.7%). Although 1H-NMR spectroscopy showed clear changes in egg yolk composition between E0 and E10, there was no line effect. In contrast, 1H-NMR analysis performed on amniotic fluid at embryonic day 10 (E10) clearly discriminated the two lines. The amniotic fluid of pHu+ was richer in leucine, isoleucine, 2-oxoisocaproate, citrate and glucose, while choline and inosine were more abundant in the pHu− line. Our results highlight quantitative and qualitative differences in metabolites and nutrients potentially available to developing embryos, which could contribute to metabolic and developmental differences observed after hatching between the pHu+ and pHu− lines.